(3efJgi GdWdH aj JMbjb GdePgHs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3eMeO Hf GdedG eMSfs)
(3ChdgG (B:s
(3ChdgG(B: (3aj GdRcGI hGdNeS hajg ebOeI hebGUO, CeG GdebOeI aajgG aUhd, GdaUd GdChd aj eGgjJgG , GdRcGI aj GddZIs
(3BNQgG (B:s
(3BNQgG(B: (3Kf SCdfj Yf YjGdj aCNHQJg HeHdZge aCeQ dj hdge HeG jbhJfG haVkdG aeG QCjJ aj Yedg NQGLG eG OGe MjG hdG bWYfj UdJg MJi eGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 227s
(3GdPQjYI, L (B23: 8s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis